Functions of endosomal trafficking in Drosophila epithelial cells - Leibfried, Andrea; Bellaïche, Yohanns (Current opinion in cell biology, 2007)
The mechanisms underlying endosomal trafficking have been mostly dissected in yeast and mammalian tissue culture cells. Here, we review recent advances in the understanding of the role of endosomal trafficking in Drosophila epithelial cells. We focus on endosomal pathways that control cell polarization, cell growth, cell fate and epithelial cell rearrangement. We expect that mechanistic studies in mammalian cells and functional studies in invertebrates will continue to synergize to provide a comprehensive view of the role of endosomal trafficking in epithelial tissue organization and functions.
Gesehen am 08.05.2023